2020
DOI: 10.1016/j.jclepro.2019.119648
|View full text |Cite
|
Sign up to set email alerts
|

The progressive adoption of a circular economy by businesses for cleaner production: An approach from a regional study in Spain

Abstract: The literature on the circular economy at the micro-level has mainly focused on the analysis of the circular business model and implementation of different circular-related practices, but the process of adoption by businesses of the circular economy is still under investigation. Therefore, through a study in the region of Aragón, Spain, the main circular economy-related activities implemented by a sample of 52 businesses are classified into four levels as an approach to the change process that firms can underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 87 publications
(141 reference statements)
4
71
1
2
Order By: Relevance
“…Many academicians (e.g. Cazaudehore et al., 2019 ; Ling et al., 2015 ; Nachiappan and Muthukumar, 2010 ; Wang, 1999 ; Wei et al., 2019 ) have also acknowledged that COD level can be reduced with the deployment of modern and eco-friendly machinery/production plants ( Aranda-Usón et al., 2020 ; Cesar da Silva et al., 2021 ; Ware, 2021 ). Particularly, Nachiappan and Muthukumar (2010) have explored various innovative and hybrid techniques for reducing COD level in the textile sector.…”
Section: Research Methodology and Data Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Many academicians (e.g. Cazaudehore et al., 2019 ; Ling et al., 2015 ; Nachiappan and Muthukumar, 2010 ; Wang, 1999 ; Wei et al., 2019 ) have also acknowledged that COD level can be reduced with the deployment of modern and eco-friendly machinery/production plants ( Aranda-Usón et al., 2020 ; Cesar da Silva et al., 2021 ; Ware, 2021 ). Particularly, Nachiappan and Muthukumar (2010) have explored various innovative and hybrid techniques for reducing COD level in the textile sector.…”
Section: Research Methodology and Data Analysismentioning
confidence: 99%
“…Implementation of CPP at company level is a preventive approach, which is primarily aimed to rein in the environmental menaces caused by modern industrialization ( Adapa, 2018 ; Andrews et al., 2002 ; Antero et al., 2020 ; Costa et al., 2021 ; Shi et al., 2021 ). Implementation of CPP can be embedded throughout the product lifecycle ( Aranda-Usón et al., 2020 ; Augusto de Oliveira et al., 2019 ; Jakhar, 2015 ) as it encompasses product design ( Cui et al., 2020 ; de Guimarães et al., 2017 ), product delivery ( Giannetti et al., 2008 ; Hens et al., 2018 ) and product recycling etc. ( Retta, 1999 ; Sousa-Zomer et al., 2018 ; Yin et al., 2020 ) with an aim to minimize their communal impact on our environment ( Li et al., 2019 ; Pazienza and De Lucia, 2020 ; Yusup et al., 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A key principle of the circular economy (CE) is that energy is powered via renewable sources [1], leading to significant reductions in fossil-fuel consumption [2,3] and greenhouse gas (GHG) emissions [4]. Additionally, some authors argued that the CE also shifts toward the use of waste-derived resources in value chains [5], while companies undertaking activities related to the CE introduced the consumption of renewables [6,7]. Haas et al (2015) indicated that strategies targeting the CE are shifting from fossil fuel to renewable energy sources and translating efficiency gains into a reduction in the overall level of resource consumption [2].…”
Section: Introductionmentioning
confidence: 99%